2020
DOI: 10.4081/monaldi.2020.1439
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation activities during the COVID-19 pandemic in Italy. Position Paper of the AICPR (Italian Association of Clinical Cardiology, Prevention and Rehabilitation)

Abstract: The COVID-19 outbreak is having a significant impact on both cardiac rehabilitation (CR) inpatient and outpatient healthcare organization. The variety of clinical and care scenarios we are observing in Italy depends on the region, the organization of local services and the hospital involved. Some hospital wards have been closed to make room to dedicated beds or to quarantine the exposed health personnel. In other cases, CR units have been converted or transformed into COVID-19 units.  The present document aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 59 publications
0
28
0
3
Order By: Relevance
“…The Ti-To home-based program, designed to overcome the barriers to exercise in an area with an aging index almost double the Europe mean value [19,34], simply relying on the telephonic monitoring passed the test during the COVID-19 epidemic. Even if social frailty, i.e., reduced connections to society and little social activity, may be correlated with reduced physical function [35,36], the program was able to ensure stable or improved function in a population with disability that was exposed to strict movement restrictions. However, the reduced sample size is a limitation of this observation.…”
Section: Discussionmentioning
confidence: 99%
“…The Ti-To home-based program, designed to overcome the barriers to exercise in an area with an aging index almost double the Europe mean value [19,34], simply relying on the telephonic monitoring passed the test during the COVID-19 epidemic. Even if social frailty, i.e., reduced connections to society and little social activity, may be correlated with reduced physical function [35,36], the program was able to ensure stable or improved function in a population with disability that was exposed to strict movement restrictions. However, the reduced sample size is a limitation of this observation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of inspiratory muscle training as an adjunct to pulmonary rehabilitation should also be considered and the importance here is eloquently described in the context of COVID-19 and future pandemics by Severin et al 28 There is additional evidence to support the use of cardiac rehabilitation in COVID-recovered patients whose underlying cardiac conditions have been exacerbated. 29 Beyond this, there is an ongoing need to continue rehabilitation services for those with non-COVID-related indications for referral, with added protective measures to prevent viral spread among these high-risk individuals.…”
Section: The Need For Bespoke Cardiorespiratory Rehabilitation Programentioning
confidence: 99%
“…In contrast, social isolation during the pandemic may result in HF destabilizations and adverse events due to changes in dietary habits such as processed food and lifestyle behaviours (decreased physical activity levels) 54 as well as quarantine-induced stress resulting in depression, social isolation, and behavioural addiction disorders. 55 To improve patient access and confidence in attending care facilities, it has been demonstrated that relocating HF services to isolated areas of admission or peripheral specialty units has prevented transmission of COVID-19 in advanced HF and cardiac transplantation patients and needs to be considered more widely to protect and promote outpatient visits. 56 For example, colour-coded zones have been implemented in an HF unit in Milan, Italy, to ensure isolation of infected, suspected, and no-symptom patients.…”
Section: Heart Failure Hospitalizationmentioning
confidence: 99%